Comparison of post-COVID symptoms in patients with different severity profiles of the acute disease visited at a rehabilitation unit. - Jean Claude Perrot; Macarena Segura; Marta Beranuy; Ignasi Gich; Mª Josepa Nadal; Alberto Pintor; Jimena Terra; Eliot Ramirez; Luis Daniel Paz; Helena Bascuñana; Vicente Plaza; Mª Rosa Güell-Rous (PLoS ONE)
Background and aim Studies in the literature suggest the severity of COVID-19 may impact on post-COVID sequelae. We retrospectively compared the different patterns of symptoms in relation to the severity of acute COVID-19 in patients visited at our post-COVID rehabilitation unit. Methods We compared respiratory, muscular, cognitive, emotional, and health-related-quality-of-life (HRQoL) measures in three groups of post-COVID patients: those who had not required hospitalization for the acute disease, those who had been admitted to a general hospital ward, and those who had been admitted to the ICU. The main inclusion criteria were persistent dyspnoea (mMRC ≥2) and/or clinical frailty (scale value ≥3). Results We analyzed data from 178 post-COVID patients (91 admitted to the ICU, 60 to the ward, and 27 who had not required admission) at first visit to our post-COVID rehabilitation unit. Most patients (85.4%) had at least one comorbidity. There were more males in all groups (58.1%). ICU patients were older (p<0.001). The most frequent symptoms in all groups were fatigue (78.2%) and dyspnea (75.4%). Muscle strength and effort capacity were lower in the ICU group (p<0.001). The SF36 mental component and level of anxiety were worse in patients not admitted to the ICU (p<0.001). No differences were found between groups regarding respiratory pressure but 30 of 57 patients with a decrease in maximum inspiratory pressure had not required mechanical ventilation. Conclusion Clinical profiles of post-COVID syndrome differed between groups. Muscle parameters were lower in the ICU group but patients who had not needed ICU admission had worse anxiety and HRQoL scores. Many patients who had not required mechanical ventilation had respiratory muscle weakness. Trial registration ClinicalTrials.gov Identifier: NCT04852718.